Neurospora alcoy linkage tester stocks with group VII marked, and their use for mapping translocations - David D. Perkins (Fungal Genetics Reports, 1991)
The original alcoy strains (T(I;II)4637 al-1; T(IV;V)R2355, cot-1; T(III;VI)1, ylo-1. Perkins et al. 1969 Genetica 40:247-278) contain three unlinked translocations tagged with markers that can be conveniently scored by inspection, without transfer. Linkage group VII is not involved in any of the translocations and was not marked. Failure to show linkage to an alcoy marker implied that the unknown was either in linkage group VII or was far removed from a marker in one of the marked groups, I-VI.